Mycobacterium tuberculosis infection in a free‑ranging urban dog from Argentina - Marfil, Maria Jimena (2022)
Mycobacterium bovis and Mycobacterium avium are the most important Mycobacteria isolated from diseased dogs, but Mycobacterium tuberculosis can be isolated as well, especially when close contact with humans exists. Free ranging street dogs may carry zoonotic diseases, being a potential health risk to new owners after adoption. In this study, the clinical case of a dog affected by Mycobacterium tuberculosis is described. A six-year-old bitch that had been living with a homeless man was rescued and put for adoption in dog shelter. After being adopted, her health declined, and abdominal ultrasound and exploratory laparoscopy were performed. A tuberculosis-like lesion in the liver was biopsied and histopathological, bacteriological, and molecular analyses were carried out. Then, the animal was euthanized and necropsied, and disseminated macroscopic tuberculosis-like lesions were observed in abdominal organs. Mycobacterium presence was confirmed by histopathological and bacteriological methods. Genotyping identified a SIT-1228 Mycobacterium tuberculosis strain. Notification to the sanitary authorities was performed and the couple that had contact with the dog were alerted and sent to the hospital for assessment, as Mycobacterium tuberculosis is a primary pathogenic agent for humans. The epidemiology in this clinical case is unclear, but the most likely source of infection might have been consumption of sputum contaminated food during the years that this bitch lived with the homeless man, because this person had died with chronic respiratory symptoms. Veterinarians must consider this disease and perform a complete diagnosis when dogs that used to live on the streets show nonspecific clinical signs.